Pengaruh Citra Merek, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Smartphone Samsung Di Kota Semarang - AisNandi, Gusti; Amron, Amron (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aimed to analyze the influence of brand image, price, and product quality on the purchase decision of Samsung smartphones in Semarang City. A quantitative approach was employed, involving 100 respondents who were Samsung smartphone users residing in Semarang. Data were collected through questionnaires and analyzed using classical assumption tests and multiple linear regression analysis. The results revealed that brand image, price, and product quality positively and significantly influenced the purchase decision of Samsung smartphones. This implies that the better the brand image, the more affordable the price, and the higher the product quality, the more it will increase consumer purchase decisions toward Samsung smartphones in Semarang. This research provides practical implications for companies to continuously build a positive brand image, set competitive prices, and improve product quality to attract consumer purchase interest.